Strategi pengembangan objek wisata pemandian air panas di desa semangat gunung kabupaten karo provinsi sumatera utara - Prawira, Anak Agung Gede Oka Ananta (Jurnal Kepariwisataan dan Hospitalitas; Vol 8 No 2 (2024): Vol.8,No.2,2024, 2025)
The aim of this research is to analyze the impact of the Spirit Mountain Village hot spring tourist attraction on the local economy and social order. Starting in April 2023, this research uses questionnaires as its main research tool in Selamat Gunung Village, Merdeka District. Thirty people became the research sample. SWOT analysis in the form of strengths, weaknesses, opportunities and threats was used in this research. This investigation examines the inner workings of the Spirit Mountain Village Hot Springs tourist attraction and the elements that emerge from the outside world. Based on SWOT analysis using qualitative and quantitative techniques of internal and external variables, it is known that the Spirit Mountain Village hot spring tourist attraction has a positive impact on the socio-economic impact of the community. Keywords: Tourist Attractions, Hot Springs, SWOT Analysis, Gunung Spirit Village, Socio-Economics.